Genotoxicity of Three Micro/Nanocelluloses with Different Physicochemical Characteristics in MG-63 and V79 Cells - Ventura, Célia (2022)
Background: Nanocellulose is an innovative engineered nanomaterial with an enormous potential for use in a wide array of industrial and biomedical applications and with fast growing economic value. The expanding production of nanocellulose is leading to an increased human exposure, raising concerns about their potential health effects. This study was aimed at assessing the potential toxic and genotoxic effects of different nanocelluloses in two mammalian cell lines; (2) Methods: Two micro/nanocelluloses, produced with a TEMPO oxidation pre-treatment (CNFs) and an enzymatic pre-treatment (CMFs), and cellulose nanocrystals (CNCs) were tested in osteoblastic-like human cells (MG-63) and Chinese hamster lung fibroblasts (V79) using the MTT and clonogenic assays to analyse cytotoxicity, and the micronucleus assay to test genotoxicity; (3) Results: cytotoxicity was observed by the clonogenic assay in V79 cells, particularly for CNCs, but not by the MTT assay; CNF induced micronuclei in both cell lines and nucleoplasmic bridges in MG-63 cells; CMF and CNC induced micronuclei and nucleoplasmic bridges in MG-63 cells, but not in V79 cells; (4) Conclusions: All nanocelluloses revealed cytotoxicity and genotoxicity, although at different concentrations, that may be related to their physicochemical differences and availability for cell uptake, and to differences in the DNA damage response of the cell model.